Factors influencing Users’ Perception on Yangon Bus Service and Origin-Destination Estimation for Bus Trips in Yangon City - Khin, May Thu Zar; Kyaw , Nyan Myint; Aye, Moe Thet Thet (The Indonesian Journal of Computer Science, 2026)
Urban public transportation in Yangon faces challenges such as overcrowding, irregular service, and mismatched supply and demand, affecting passenger satisfaction. This study evaluates the Yangon Bus Service (YBS) by combining users’ perception analysis with Origin–Destination (O–D) estimation. Surveys measured passenger satisfaction with service attributes, and O–D matrices assessed travel patterns across the city. Stepwise multiple linear regression showed that comfort (0.107), bus route (0.106), and bus stop cleanliness (0.432) positively influence satisfaction, while bus fare (-0.117) has a negative effect. Travel activity is concentrated in Yangon's central areas, reflecting the city’s monocentric structure and generating high daily bus demand. The findings provide insights to improve YBS by identifying factors affecting satisfaction and travel demand, guiding service enhancements, optimizing operations, and increasing ridership.